Nematophin, an Antimicrobial Dipeptide Compound From Xenorhabdus nematophila YL001 as a Potent Biopesticide for Rhizoctonia solani Control - Zhang, Shujing; Liu, Qi; Han, Yunfei; Han, Jinghua; Yan, Zhiqiang; Wang, Yonghong; Zhang, Xing (Frontiers in Microbiology, 2019)
Abstract: This study was conducted to purify and identify metabolites of antimicrobial activity against phytopathogens from Xenorhabdus nematophila YL001. Three dipeptide compounds were purified from its cell-free cultural broth and identified as (±)-nematophin, cyclo (L-Pro-Gly) and N, N’-dimethyl-cyclo (L-Phe-L-Leu). Nematophin demonstrated a wider antifungal spectrum than the other two compounds. It also exhibited strong inhibitory effects on mycelial growth of Rhizoctonia solani and Phytophthora infestans with EC50 values of 40.00 and 51.25 μg/mL, respectively. Its (S)-configuration structure ((+)-nematophin) was also synthesized and exhibited higher antimicrobial activity than the enantiomeric mixture. The detached leaf assay revealed that nematophin possessed significant preventive and curative efficacy against R. solani on broad bean leaves showing the corresponding control efficacies of 93.01% and 94.93% at 1000 µg/mL, comparable to those of a chemical fungicide (carbendazim) at 500 µg/mL. Besides, the pot experiments indicated that nematophin could effectively inhibited the disease extension on rice and broad bean plants caused by R. solani. Nematophin also exerted some adverse influences on the sclerotial development of R. solani by dramatically suppressing their formation and maturation at 40.00 µg/mL, as well as their germination at 15.00 µg/mL. Morphological and ultrastructural observations showed that the hyphae of R. solani became twisted, shriveled, and deformed at the growing points after exposure to nematophin at 40.00 μg/mL, and that the subcellular fractions also became abnormal concurrently, especially the mitochondrial structure. These results indicate that nematophin has great potential to be used as a bio-pesticide in agricultural production.